The Articulation of a Maqāṣidī Approach in Hasyim Asy’ari’s Qur’anic Interpretation - Ali Fikri, Abdul Aziz; Ida Kurnia Shofa (Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
This article aims to examine the dimensions of maqāṣid-based interpretation in the thought of Hasyim Asy’ari. Despite his prominence in Indonesian Islamic scholarship, Hasyim Asy’ari has seldom been examined through the lens of Qur’anic hermeneutics. Yet, his writings frequently cite Qur’anic verses to substantiate and legitimize his intellectual positions. This study addresses two central questions, namely, how Hasyim Asy‘ari uses and interprets the Qur’an as articulated in his books Ādāb al-‘Ālim wa al-Muta‘allim and Al-Tibyān fī al-Nahy ‘an Muqāṭa‘ati al-Arḥām wa al-Aqārib wa al-Ikhwān, and how the maqāṣidī dimensions are reflected in both works. By using textual analysis, the study reveals two important points. First, Hasyim Asy‘ari’s interpretive framework aligns with the maqāṣidī-based approach, wherein the Qur’anic verses are interpreted to substantiate specific religious positions. However, his method reflects elements of thematic exegesis (mauḍū‘ī), while in terms of sources and interpretive orientation, his approach can be classified as reason-based interpretation (tafsīr bi al-ra’y), exhibiting an adabī-ijtimā‘ī style that emphasizes socio-ethical dimensions. Second, with regard to the discernible dimensions of maqāṣidī, Hasyim Asy‘ari’s Qur’anic interpretation resonates with the broader objectives of Islamic law, particularly the values of al-‘adālah (justice), al-ḥurrīyah (freedom), al-mas’ūlīyah (responsibility), and al-insānīyah (human dignity).